Entre cenas, enredos e roteiros: a formação humana pela via da criação artística: a experiência do grupo de teatro da UNIPOP - SOUSA, Vera Solange Pires Gomes de (2007)
This study establishes the interface of the theater and education with the perspective of evidencing the significant elements of the educational dimension of the Theater of the Institute Popular University - UNIPOP. He/she/you elapses, therefore, of two movements that are interlaced. The first concerns the origin of the Group of Theater of Unipop. The second, he/she goes back to the educational dimension of that Group. The study has your methodological important in the qualitative research. This Dissertation discusses the human formation starting from the experience lived by the Group of Theater of the Popular University (UNIPOP), tends as objective verifies the significant elements of the educational dimension of the Theater of that institution. He/she/you breaks of the presupposition that the theater, as artistic language, it can contribute to human formation through the artistic creation, being, therefore, the theatrical practices potentially educational practices. The principal authors that supplied basic ideas to the theoretical constitution of this study were Freire, Baron and Boal. In the beginnings of the qualitative research, but specifically with inspiration in the etnometodologia, I adopt as procedures of search of information the observation, the documental analysis, the interview, illustrations and pictures as illustration of events. In the focus of the relationship theater and education, the significant elements of the educational dimension of the Group of Theater of Unipop, that emerged during the investigation highlight: life history as scene element, the expansion of the theater and the process collective. The analysis of the significant elements of the educational dimension of the Group of Theater of Unipop makes possible us to understand that the theater, as artistic language, it can contribute to the human formation through the artistic creation. Being, therefore the theatrical practices potentially educational practices, but this is only possible reason the Group of Theater of effective Unipop an education with sensibility. The theatrical experience evidences an interface between theater and education where primordial focus is the human formation for the road of the artistic creation.